New Insights Into Potential Benefits of Bioactive Compounds of Bee Products on COVID-19: A Review and Assessment of Recent Research - Elmahallawy, Ehab Kotb; Mohamed, Yasser; Abdo, Walied; El-Gohary, Fatma A.; Ahmed Awad Ali, Shaimaa; Yanai, Tokuma (Frontiers in Molecular Biosciences, 2021)
The recent emergence of COVID 19 represents one of the biggest challenges facing the world today. Despite the recent attempts to understand the epidemiological pattern and pathogenesis of the disease, the detailed data about the physiology and pathology of the disease is still out of reach. Moreover, the lack of vaccine makes an urgent call for developing proper intervention strategy against the virus. Importantly, identification of novel molecules that target replication of the virus represents one of the promising strategies for control this pandemic crisis. Among others, honey bee products contain numerous bioactive compounds such as propolis and several phenolic compounds that possess a wide range of therapeutic properties for combating various pathological disorders and infectious agents. The intention of the present review is to highlight about the stages of SARS-CoV-2 lifecycle, the molecular mechanisms explaining the health benefits of honey bee products on COVID 19 physiology and pathology and the possible limitations. Further future research is suggested to explore more about bee natural bioactive compounds as potential candidates against SARS-CoV-2.